PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DELI SERDANG DI ERA COVID-19 DISEASE - Tria Novella Rambe; Mardiansyah Mardiansyah (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
The Disdukcapil of Deli Serdang Regency made a policy based on the Letter of the Minister of Administrative and Bureaucratic Reform Number 34 of 2020 concerning Adjustment of the Work System of the State Civil Apparatus in Efforts to Prevent Corona Virus Disease (Covid-19) in Government Agencies.  which stated that for Deli Serdang people who wanted to take care of administration at the Population Service office and no longer needed to come to the office.  People simply use email when submitting an administrative application.  So the purpose of this study was to find out how the Public Service at the Department of Population and Civil Registration of Deli Serdang Regency was in the Corona Virus Disease (Covid-19) Era.  This type of research in this study uses a descriptive method, with a qualitative approach.  And it can be concluded that there is a change in the service system at the Disdukcapil Deli Serdang Regency.  To anticipate the spread of the corona virus-19, the Disdukcapil of Deli Serdang Regency approached the sub-district for the processing of e-KTP and KK (Family Cards), and the Disdukcapil of Deli Serdang Regency had the SADOKO Innovation program (Ready for Population Documents).